Mining Goes Digital : Proceedings of the 39th International Symposium 'Application of Computers and Operations Research in the Mineral Industry' (APCOM 2019), June 4-6, 2019, Wroclaw, Poland - Christoph Mueller; Winfred Assibey-Bonsu; Ernest Baafi; Christoph Dauber; Chris Doran; Marek Jaszczuk; Oleg Nagovitsyn (CRC Press, 2019)
The conferences on ‘Applications for Computers and Operations Research in the Minerals Industry'(APCOM) initially focused on the optimization of geostatistics and resource estimation. Several standard methods used in these fields were presented in the early days of APCOM. While geostatistics remains an important part, information technology has emerged, and nowadays APCOM not only focuses on geostatistics and resource estimation, but has broadened its horizon to Information and Communication Technology (ICT) in the mineral industry. Mining Goes Digital is a collection of 90 high quality, peer reviewed papers covering recent ICT-related developments in:- Geostatistics and Resource Estimation- Mine Planning- Scheduling and Dispatch - Mine Safety and Mine Operation- Internet of Things, Robotics- Emerging Technologies - Synergies from other industries - General aspects of Digital Transformation in MiningMining Goes Digital will be of interest to professionals and academics involved or interested in the above-mentioned areas.